PENGEMBANGAN KOPERASI SAMPAH UNTUK PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA JELANTIK KABUPATEN LOMBOK TENGAH - Humairo Saidah; Shofia Rawiana; Ratna Yuniarti; Ida Ayu Oka Suwati Sideman; Desi Widianty (Jurnal Abdi Insani, 2022)
The "Sapu sae" waste cooperative is a joint effort of community groups in Jelantik Village to collect waste, especially plastic waste, to overcome the problem of plastic waste while improving the welfare of the residents. However, this cooperative is currently no longer operating due to various reasons. Difficulty in collecting waste due to residents' refusal, lack of administrative and financial management capabilities and unclear management of the cooperative are the main reasons why this cooperative is unable to survive. This activity aims to revive village waste management activities. This service activity uses a solution approach method for cooperative problems. The activities are carried out in several stages, including the revitalization of cooperatives, simple bookkeeping and finance training for administrators, waste management training for members, providing minimal assistance for cooperatives and closing with mentoring and evaluation. This activity has been carried out and received a warm welcome from the Jelantik Village community. The waste cooperative has been revived with new legal administrators who have been given bookkeeping training. Cooperative members were also given training in making handicrafts made from waste. Service activities also provide minimal means for carrying out cooperative activities in the form of garbage collection sacks, member savings books and cooperative administration book packages. This activity has been evaluated and shows positive developments with the return of the cooperative and increasing public awareness in waste management.